Britain and the chevaline project: The hidden nuclear programme, 1967–82 - Kris Stoddart (Journal of Strategic Studies, 2003)
With the words quoted above, the new Secretary of State for Defence in the Thatcher government revealed for the first time the existence of a project that have remained a closely guarded secret, even from amny Cabinet members of four governments, since the late 1960s. Despite the passage of more thatn 20 years since Mr Pym's announcement, the story of the Chevaline project still remains largely unknown outside a small group of select politicians, officials and scientists. This article sets out to use recently declassified documents and what is in the public domain to tell the story of Chevaline from the secret debates about the need to improve Britain's Polaris deterrent force shortly after it was deployed in the late 1960s to the official announcement of the project in 1980 and its eventual operational deployment in 1982. In particular, attention is focused on three main questions: Why was the project kept secret for so long? Why did the improvement programme take so long to come to fruition? Why, given the spiraling costs involved, was it not cancelled? In order to consider these questions relating to what Pym described as ‘the front end’ of the Polaris missile, it is necessary to begin by looking at the background to the project.